Ethical decision support system based on hermeneutic view focus on social justice - Alesyanti, A; Ramlan, R; Hartono, H; Rahim, Robbi (International Journal of Engineering and Technology, 2018)
Truth and justice can not be separated from the substance and purpose of the law. Law in the sense of right and just is a concept to be con-sidered. Only through a fair legal system and the right that people will be able to live peacefully toward a physical and spiritual wellbeing. The role of computer science is to produce a decision support system to determine whether a person has behaved ethically especially in terms of the rules of truth and justice from a hermeneutic point of view by using decision support systems. The decision support system will be designed using the Analytical Hierarchy Process (AHP) method. The results of this study are expected to facilitate in the determination of human behavior in terms of truth and justice.Â Â